Cliché and repetition: McLuhan understanding modernism. Issue 9 (2nd September 2021) - Nicholls, Peter
ABSTRACT: Marshall McLuhan's literary essays of the 1940s and 1950s have been largely eclipsed by his fame as an early media theorist, though they constitute a rich repository of innovative readings of modernist writing and its nineteenth-century pre-history. At a time when contemporary critics are increasingly exercised about the continuing hegemony of modernism as the impossible arbiter of the new and the original, McLuhan's early essays offer a series of bold hypotheses about the work of Mallarmé, Joyce, Pound, Eliot and Lewis that propose a 'retrogressive movement' of the modernist intelligence that far from agonizing about the authenticity of the 'new' attribute a kind of cognitive 'retracing' to imaginative activity. This 'retrieval' of the past is not, however, the product of leisurely recollection but of a fascination with discontinuity. One might expect McLuhan, as media theorist, to be preeminently concerned with vision and visual space, but it is rather the auditory sense he values for the access it gives to experiences of discontinuity and dynamism. Current concerns about the inhibiting character of modernism as a 'tradition of the new' thus have no place here, as McLuhan discards dialectic in favor of a sort of pure instantaneity.